La libertad de elección en educación, ¿finalidad o instrumento de las reformas educativas? - Villamor Manero, Patricia (Revista Complutense de Educación, 2007)
The purpose of this paper is to analyze the relationships between school choice as an instrument or as an objective of the educational reforms and their success in the creation of diversity in the educational system. The diversity is the most important factor in the school choice. In order to analyze these relationships, the cases of Canada, Chile and New Zealand, and its implications in the structure, autonomy, and management of their educative systems, will be studied. This international approach tries to be representative enough of the different contexts that have lead to promote the school choice in education with very different objectives and methodologies.